Data for decision-making for sustainable food systems transformation in the Eastern Cape of South Africa: what is needed? - Karan, Romyne; Mowlds, Sinead; McKeown, Peter C.; Lundy, Mark; Spillane, Charles (Frontiers in Sustainable Food Systems, 2023)
Transforming global food systems to promote food and nutritional security can help alleviate both poverty and ill-health, and support sustainable development. Such transformations need to be tailored and sensitive to the vulnerabilities and needs of marginalised communities yet are hindered by knowledge gaps. In particular, the food and nutrition security needs of the most vulnerable are often poorly understood, as are the policy frameworks and resource requirements associated with meeting their needs. To aid the development of frameworks to address these gaps, we review the current state of indicators relating to food systems for the improvement of food and nutrition security at the national and sub-national levels in South Africa. We identify gaps in the decision-making data in South Africa, including absence of food and nutrition security indicators. Integration of the South African Multidimensional Poverty Index and Food System Dashboard indicators could help address this, especially if applied at a sub-national level. Participatory food system mapping could also link data collection with system-level interactions and feedback loops to inform sub-national stakeholders in achieving food and nutritional security.